THE LOGIC OF RECONSTRUCTION OF THE NEW WORLD ORDER AND THE LEGITIMISATION OF POST-TRUTH IN LEGAL DISCOURSE - Kharchenko, Serhii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
The problem of world order is considered as a very urgent one. It raises the issue of the development prospects of of the global social system, which is being reconstructed intensively due to the fact that its various segments are becoming less coordinated, balanced, sustainable. This study aims to conceptualize the mechanisms behind the construction of post-truth technology within the framework of restructuring the new world order, as well as to analyse the procedures that legitimize post-truth within legal discourse.